Structural Comparison of α-agarase (α-AgaD) from Thalassomonas sp. LD5: An in-silico study: Structural Comparison of α-agarase (α-AgaD) from Thalassomonas sp. LD5 - Oyewusi, Habeebat Adekilekun; Oladipo, Oluwatosin; Abdul Wahab, Roswanira; Adekilekun , Habeebulahi Ajibola; Wayan Gunam, Ida Bagus; Huyop, Fahrul (Journal of Tropical Life Science, 2025)
The significance of agarase enzymes spans various high-value industries, including food, cosmetics, and medicine. These enzymes play a crucial role in the hydrolysis of agar to produce bioactive oligosaccharides, enabling wide-ranging applications across multiple fields. Among them, α-AgaD is a novel α-agarase enzyme produced by the Thalassomonas sp. LD5 strain. However, the structural and functional characteristics of α-AgaD within biological systems remain largely unexplored. This study therefore aims to provide a comprehensive in silico analysis of α-AgaD, focusing on its physicochemical properties, phylogenetic relationships, secondary structure composition, and 3D homology modelling. A range of computational tools was employed to validate the findings and enhance the structural understanding of this newly identified α-AgaD enzyme. The α-AgaD protein consists of 1,466 amino acids with a molecular weight of 158,787.82 Da. It has a theoretical isoelectric point (pI) of 4.14, indicating an overall acidic nature. Structural analysis revealed that alpha helices and random coils are the predominant secondary structures. Hydrophobic amino acids were more abundant than hydrophilic ones, with glycine accounting for approximately 10.4% of the total residues. The protein's aliphatic index was 72.05, and the instability index was 28.28, suggesting that α-AgaD is stable and likely to maintain its structure across a wide temperature range. Three-dimensional models of α-AgaD were constructed using I-TASSER, NCBI-PDB, SWISS-MODEL, and AlphaFold2, and subsequently validated using ERRAT, Verify3D, and PROCHECK. Among the models generated, AlphaFold2 produced the most accurate prediction, with nearly all amino acid residues located in the preferred regions of the Ramachandran plot. This further confirmed the reliability and quality of the refined models. The in silico structural analysis of α-AgaD offers valuable insights into the enzyme’s primary sequence, functional domains, and overall structural architecture, enhancing our understanding of α-agarase from Thalassomonas sp. LD5.